2014
DOI: 10.1159/000362388
|View full text |Cite
|
Sign up to set email alerts
|

Development of Normal Gestational Ranges for the Right Myocardial Performance Index in the Australian Population with Three Alternative Caliper Placements

Abstract: Objectives: To construct gestational age-adjusted reference ranges for the right fetal modified myocardial performance index (RMPI) in an Australian population and to assess the influence of valve click caliper position on constituent time intervals and the RMPI. Methods: A prospective cross-sectional study of RMPI from 235 normal fetuses at 17-38 weeks of gestation was performed. Two Doppler waveforms were obtained: tricuspid and pulmonary valves for ‘a' and ‘b' readings, respectively. The ultrasound machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Our findings showed that preceding 18 weeks gestation, mean LMPI and RMPI were identical within the same fetus (∼0.40), after which the difference between them increased, consistent with our previous normal range studies showing the RMPI increasing at a steeper rate with gestation [3,11]. The relative increase in RMPI (and hence DMPI) may reflect the physiological decrease in right ventricular compliance in comparison to the left with advancing gestation [21].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings showed that preceding 18 weeks gestation, mean LMPI and RMPI were identical within the same fetus (∼0.40), after which the difference between them increased, consistent with our previous normal range studies showing the RMPI increasing at a steeper rate with gestation [3,11]. The relative increase in RMPI (and hence DMPI) may reflect the physiological decrease in right ventricular compliance in comparison to the left with advancing gestation [21].…”
Section: Discussionsupporting
confidence: 89%
“…We calculated the DMPI normal range by measuring the peak of valve clicks, as our previous results demonstrated this to be most objective and repeatable [3,11,29,30]. In the current study, the DMPI had an ICC of 0.79 (95% CI 0.75-0.83), and repeatabilities for LMPI and RMPI were relatively unchanged.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…50 th percentile ranged from 0.45 at 12 to 0.57 at 40 weeks of gestation, respectively. Meriki et al [28] determined a reference range for Mod-MPI in 235 Australian singleton pregnant women between 18 and 37 weeks of gestation. 50 th percentile ranged from 0.48 at 18 to 0.57 at 37 weeks of gestation, respectively.…”
Section: Discussionmentioning
confidence: 99%